UZASADNIENIA AKSJOLOGICZNE W ORZECZNICTWIE TRYBUNAŁU KONSTYTUCYJNEGO - Kordela, Marzena (Wydział Prawa i Administracji UAM, 2000)
Sentencing in cases of conformity of lower ranked normative acts with acts which are superior within the legislative hierarchy the Constitutional Tribunal is usually having recourse to three following types of motivation statements: descriptive statements (expresses in phrases), directional statements (in form of norms of behavior) and, finally, appraisals. Taking into consideration some visible regularities in citing appraisals by Constitutional Tribunal, or even sequences o f such appraisals given for to prove axiological rationality of the decisions taken by the Tribunal - one can distinguish characteristic types of such reasons; i.e. reasons based on interference of the type „from the whole to a detail”, reasons built up in so-called negative inferences, next - reasons based on inferences focused on „the essence itself’ of a given regulation, reasons based on inferences appealing to a „definition” o f particular values and also - reasons based on: inferences of reductive character, admitted spirit of consequence of the legislator in his appraisals, inferences based on preferential questions. Despite of such a heterogeneity (from formal logic up to the sphere of applying the law) all the above cited types of axiological reasons can be reduced to one scheme that prejudges their validity in law - since all them are provided with the quality of being rational and objective.
AXIOLOGICAL REASONS FOR THE JURISPRUDENCE OF THE CONSTITUTIONAL TRIBUNAL